Penegakan Hukum dalam Kajian Law and Development: Problem dan Fundamen bagi Solusi di Indonesia - Juwana, Hikmahanto (Indonesian Journal of International Law, 2006)
Law enforcement holds an important role in Indonesian legal system. How strict the law is enforced will determine the existence of the law itself. Problems in law enforcement are multidimensional, vary interconnected, and have been abandoned ofr quite some time without any serious efforts to solve it. Those problems are the legislative drafting process, victory minded society instead of justice, money talks, law enforcement as political ride, discrimination, low quality and integrity of the human resources, nepotism and collusion, limited budget, and the interference of the media. This article gives an out which is a foundation of the reformation of the law enforcement with hope this solution can be comprehensive and not just temporary.